ORGANOLEPTIC QUALITY OF LAMB MEAT USING BATAK’S ONION EXTRACT (Allium chinense G. Don) FOR RENDANG - Asmaq, Nur; Wibowo, Fachrina (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This study aims to determine the quality of lamb meat which will be processed into rendang by assessing the organoleptic meat soaked in 10% Batak onion extract (A. chinense G. Don). The samples used in this study were Batak onion (A. chinense G. Don) and lamb meat. Lamb meat is marinated in 10% Batak onion extract at room temperature. This research was conducted by observing lamb meat and analyzed descriptively. Parameters observed were lamb meat organoleptic. The results of the research conducted showed that soaking lamb meat in 10% Batak onion extract gave the color of the meat still looking fresh with a slightly brownish effect, the aroma smelled of Batak onions and the texture was still chewy. Based on the results of this study, lamb meat soaked in 10% Batak Onion extract (A. chinense G. Don.) is suitable for use in making rendang.